ANALYSIS OF NURSING CARE IN DIABETES MELLITUS PATIENTS THROUGH DIABETIC FOOT EXERCISE INTERVENTION FOR BLOOD CIRCULATION IMPROVEMENT IN TERATAI ROOM, IHC RSU WONOLANGAN PROBOLINGGO - Putra, Kusuma Wijaya Ridi; Choirunnisak, Dilla Riksa; Fiddaroini, Fakhrun Nisa’; Puspita, Enny (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Diabetes mellitus, a chronic metabolic disease, can lead to serious complications, including impaired blood circulation in the extremities, termed diabetic foot, leading to peripheral neuropathy and poor perfusion. Objectives: This study aimed to assess the impact of diabetic foot exercise on improving blood circulation among diabetic patients. Design: This case study utilized a descriptive method on two diabetic patients in Teratai Room, RSU Wonolangan Probolinggo. Foot exercise intervention was implemented three times weekly for 15–20 minutes. Results: Both patients showed improvement in peripheral blood circulation, indicated by Ankle Brachial Index (ABI) scores within the mild obstruction range after consistent foot exercise. Conclusion: Regular diabetic foot exercises may enhance blood circulation and prevent complications among diabetes mellitus patients.